2020
DOI: 10.1039/d0dt02872j
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent polypyridyl heteroleptic CrIII complexes with high quantum yields and long excited state lifetimes

Abstract: Implementing high quantum yields and long-lived excited states lifetimes within heteroleptic luminescent Cr(III) complexes is a keystone for the design of supramolecular energy-converting devices exploiting this cheap metal. In this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 32 publications
1
35
0
2
Order By: Relevance
“…[36] C is an additional electron‐electron repulsion parameter required to calculate the energy of the 2 E state (equation S2), and using the above‐mentioned relationship, a value of 470 cm −1 is obtained for the Racah B parameter. For the previously investigated [Cr(ddpd) 2 ] 3+ and [Cr(dqp) 3 ] 3+ compounds B ‐values of 760 cm −1 and 660 cm −1 have been reported (Table 1 ),[ 5 , 9b ] falling into the typical range of Racah B parameters of Cr 3+ doped oxides, fluorides, and chlorides (600–750 cm −1 ). [37]…”
Section: Resultsmentioning
confidence: 99%
“…[36] C is an additional electron‐electron repulsion parameter required to calculate the energy of the 2 E state (equation S2), and using the above‐mentioned relationship, a value of 470 cm −1 is obtained for the Racah B parameter. For the previously investigated [Cr(ddpd) 2 ] 3+ and [Cr(dqp) 3 ] 3+ compounds B ‐values of 760 cm −1 and 660 cm −1 have been reported (Table 1 ),[ 5 , 9b ] falling into the typical range of Racah B parameters of Cr 3+ doped oxides, fluorides, and chlorides (600–750 cm −1 ). [37]…”
Section: Resultsmentioning
confidence: 99%
“…Although some chromium complexes possessing high 1 O 2 quantum yields have been reported, 61,62 their phototoxic activities are generally rather disappointing. The biological study of a Cr( iii ) complex which was expected to be very promising as a PDT PS was reported in 2019 by the Heinze and Gasser groups ( Cr-1 , Fig.…”
Section: Phototoxic First-row Transition Metal Complexesmentioning
confidence: 99%
“…Va lues of 14-15 %w ere obtained for 3 and 4 respectively,t ogether with ar ecord of 17 %f or 2.T hese values are amongt he highest values reported up to date for deuterium-free Cr III complexes in aqueous solutions. [55,[57][58][59][60][61][62] Theh ighly emissive character of…”
Section: Resultsmentioning
confidence: 99%